1980
DOI: 10.1128/iai.27.1.204-210.1980
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease-sensitive ribosomal vaccine of Pseudomonas aeruginosa

Abstract: In mice, active protection against Pseudomonas aeruginosa could be induced with two fractions derived from a crude preparation of ribosomes from P. aeruginosa. The two fractions were obtained by gel filtration chromatography of the crude ribosomal preparation on Sepharose CL-2B. In fraction I, less than 1% of the ribonucleic acid (RNA) applied to the column was recovered. Fraction II contained RNA and protein in a ratio of 1.94. The presence of ribosomes in this fraction was confirmed by analysis on a sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In particular, the function of the ribosomes in the vaccines has been discussed, since contaminating cell envelope antigens were found in several of the ribosomal preparations (6,17,18). Previous studies of this laboratory (9) showed that a ribosomal vaccine of P. aeruginosa could be prepared which was sensitive to RNase, indicating that the ribosomal RNA was required for the protective activity of this vaccine. In addition, this vaccine could induce antibodies to the cell envelope component LPS (10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the function of the ribosomes in the vaccines has been discussed, since contaminating cell envelope antigens were found in several of the ribosomal preparations (6,17,18). Previous studies of this laboratory (9) showed that a ribosomal vaccine of P. aeruginosa could be prepared which was sensitive to RNase, indicating that the ribosomal RNA was required for the protective activity of this vaccine. In addition, this vaccine could induce antibodies to the cell envelope component LPS (10).…”
Section: Resultsmentioning
confidence: 99%
“…Protective vaccines have been prepared from the ribosomes or ribosomal extracts of many different microorganisms, including Mycobacterium tuberculosis, Salmonella typhimurium, Streptococcus pneumoniae (5), and Pseudomonas aeruginosa (9,16). The diversity of the microorganisms from which protective ribosomal preparations could be prepared has raised the question of whether the ribosomes have a unique function in the induction of an immune response.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Purification of RNA. RNA was extracted from purified ribosomes as described previously (1,11,12). The purified RNA contained less than 1% protein.…”
Section: Methodsmentioning
confidence: 99%